Speed, strength & power characteristics of horizontal jumpers - Graham-Smith, P.; Brice, P. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
It is well established that approach speed on the long and triple jump runways is the single-most important determinant of performance across a wide range of ability levels (Hay, 1986; Hay, 1992). However, the relationship between speed and jump distance decreases when the range of performances is reduced. At an elite level speed is regarded as a pre-requisite, the differentiating factor between performances relates more to how well athlete control their speed when they make contact with the take-off board (and subsequent take-offs in the triple jump). In the take-off athletes typically experience vertical impact forces in the range of 7.9 to 12.6 x BW (Ramey and Williams, 1985), with ground contact times ranging from 120 to 180 ms (the higher values relating to the step and jump take-offs). It is therefore imperative that horizontal jumpers are conditioned appropriately to accept such high loading forces, be powerful and reactive, in order to generate vertical speed in such a small timescale. Graham-Smith and Lees (2002) suggested that performance is made up of three main interacting factors; speed, strength and technique (with power being a derivative of speed and strength). They added that optimal performance can only be achieved when all three factors are in 'balance'. The aim of this study was to develop a battery of tests to monitor speed, strength and power for horizontal jumpers in as functional a way as possible. The relationship between strength and power variables with speed and controlled functional performance was also investigated.